Resistance measurement and activation energies calculations of pure and platinum doped stannic oxide ceramics in air - Ibrahim, Zuhairi; Othaman, Zulkafli; Abd Karim, Mohd Mustamam; Holland, Diane (American Institute of Physics, 2007)
Pure SnO2 and Pt- SnO2 ceramics were fabricated by the dry pressing method using a pressure of 40 MPa and sintered at 1000 °C. Electrical measurements were made using an impedance analyzer, in air and temperatures between 25 °C and 450 °C. The change in resistance in both pure and paltnium-doped stannic oxide ceramics was discussed